On-line fault diagnosis and fault-tolerant operation of modular multilevel converters — A comprehensive review - He, JiangBiao; Yang, Qichen; Wang, Zheng (CES Transactions on Electrical Machines and Systems, 2020)
Modular multilevel converters (MMCs) have been one of the most broadly used multilevel converter topologies in industrial applications, particularly in medium-voltage motor drives and high-voltage dc power conversion systems. However, due to the utilization of large amount of semiconductor devices, the reliability of MMCs becomes one of the severe challenges constraining their further development and applications. In this paper, common electrical faults of the MMC have been summarized and analyzed, including open-circuit switching faults, short-circuit switching faults, dc-bus short-circuit faults, and single line-to-ground faults on the ac side. A thorough and comprehensive review of the existing online fault diagnostic methods has been conducted. In addition, fault-tolerant operation strategies for such various fault scenarios in MMCs have been presented. All the fault diagnosis and fault-tolerant operation strategies are comparatively evaluated, which aims to provide a state-of-the-art reference on the MMC reliability for future research and industrial applications.